Background and self concept of the Indochinese refugees : unaccompanied minors - Mallika Piyamada (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
The objectives of the research were to investigate the background and self-concept of the unaccompanied minors who arrived in Thailand before March 14, 1989. There are 24 subjects aged between 12-18 years old who stay in Khao I Dang Camp in Prachinburi province and Phanat Nikhom Camp in Chonburi province. A structured interview and a self-concept scale for the unaccompanied minors were developed and used for data collection during February-March 1992. The result of the research shows that: 1. The unaccompanied minors come from 3 nationalities, that are Vietnamese, Khmer, and Laotian (Hmong, Highland Laotians). There are 3 times males more than females. 2. Majority of the unaccompanied minors still have parents, siblings or relatives staying in other places which are in home countries, in the same first asylum country but different refugee camps, or in third countries. 3. Separation from parents mostly happened when they were 15 years old and younger. Separation mainly occurred during flight, death of the parents or close relative before or after escaping from home countries, and separation in refugee camps. Motivation to escape concerned chances for resettlement in third countries. 4. Majority of unaccompanied minors were staying in the camp community with other refugees. Most of them are healthy, even though around a half thinks that food and water allotments were insufficiency. 5. They spent daily-life time mostly for study Some of them feel bored and wish to go to third country for resettlement, to continue education and find good jobs as soon as possible. 6. They have position self-concept in 10 out of 12 areas in this study, which are, physical health, gender identity, intellectual ability, impulse control, self-satisfaction, motivation, goals of life, morals, relationships with others, and social attractiveness. 7. About emotional state, they have both positive and negative self-concept which were be happy individuals while sometimes have worry, fear, loneliness and guilty feelings. 8. The only one area in which they obviously have negative self concept was about material possession.